What’s cooking? The effect of temperature on the immune response - Old, Julie M.; Dixon, Brian (Frontiers in Immunology, 2025)
Animals have evolved to live in different environs, with some having developed specialised features to support survival in adverse conditions, whilst others adapt behaviourally. Temperature impacts the immune system differentially, with lower temperatures impacting the adaptive immune response, but not the innate response. A reduction in adaptive immune capacity at lower temperatures can be due to a failure to effectively assemble MHC and may be a result of modifications of the plasma membrane structure or its viscosities. Higher temperatures can be beneficial initially, but can be disruptive if excessive. Ensuring the effectiveness of the adaptive immune response through optimal temperature regulation or manipulation, where possible, may support immunological fitness, ultimately enhance the conservation and biodiversity of wildlife species, and improve welfare outcomes for production animals and ourselves.